Exploring gender differences in the EFL classroom - Durán, Norma Constanza (Colombian Applied Linguistics Journal, 2006)
This article aims to describe a case study which explores teacher and students` conceptions about gender in an EFL setting and the way they are manifested in their discourse patterns. This exploratory case study was carried out with a group of eleventh grade students and an English teacher at Liceo de la Universidad Católica high school in Bogotá Colombia. The data collected included direct observation of classroom interaction, audio and video recording of the teacher and students` interactions and interviews on the teacher’s and students` discourse. The analysis of the data revealed that in fact there are imbalances in relation to boys` and girls` participation during interaction, made manifest by verbal and nonverbal attitudes. There is also sound evidence of girls’ low self esteem in response to the lack of value and respect granted to their opinions by their male peers. Stereotypes are part of teachers’ and students’ conceptions regarding gender and thus they are maintained to a great extent. The teacher’s attitude in the classroom with respect to boys and girls also appeared to show inequality that favoured boys. The girls showed evidence of awareness of the teacher’s conscious or unconscious indifference towards them, which seemed to affect their autonomy and confidence as English language learners.